2020
DOI: 10.3390/ijms21145012
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor SCX is a Potential Serum Biomarker of Fibrotic Diseases

Abstract: Fibrosing diseases are causes of morbidity and mortality around the world, and they are characterized by excessive extracellular matrix (ECM) accumulation. The bHLH transcription factor scleraxis (SCX) regulates the synthesis of ECM proteins in heart fibrosis. SCX expression was evaluated in lung fibroblasts and tissue derived from fibrotic disease patients and healthy controls. We also measured SCX in sera from 57 healthy controls, and 56 Idiopathic Pulmonary Fibrosis (IPF), 40 Hypersensitivity Pneumonitis (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…However, because the dimer composition is very variable ( Table 3 , Table 4 and Table 5 ), it is proposed that future publications in the field should state the composition of the dimeric (or multimeric) bHLH TFs involved. As an example, in a study of the role of the bHLH TF SCX in tissue fibrosis, it was concluded that the relevant bHLH dimer is SCX/E47, as SCX by itself did not have a role in the experiments tested [ 274 ].…”
Section: Heterodimeric Interactions Among Bhlh Tfs Of Classes I Ii V and Vimentioning
confidence: 99%
“…However, because the dimer composition is very variable ( Table 3 , Table 4 and Table 5 ), it is proposed that future publications in the field should state the composition of the dimeric (or multimeric) bHLH TFs involved. As an example, in a study of the role of the bHLH TF SCX in tissue fibrosis, it was concluded that the relevant bHLH dimer is SCX/E47, as SCX by itself did not have a role in the experiments tested [ 274 ].…”
Section: Heterodimeric Interactions Among Bhlh Tfs Of Classes I Ii V and Vimentioning
confidence: 99%
“…Several prognostic staging systems for IPF have been established by clinical and physiologic variables (2)(3)(4)(5). Biomarkers in peripheral blood are also evaluated as a tool for prognosis (6)(7)(8). A recent study also revealed the role of genetic variability in the survival of IPF (9).…”
Section: Introductionmentioning
confidence: 99%
“…Genes were ranked based on the significance of the differences in expression levels. Among the most-upregulated genes, we detected several typical genes involved in the fibrotic process such as SCX ( 33 ) and POSTN ( 34 ). Notably, the upregulation of IL-11 expression (2.83-fold, P=7.2×10 -4 ) defined the dominant transcriptional response of OFs to TGF-β1 ( Figure 4A ), which was further verified at the mRNA level by qRT-PCR and at protein levels by ELISA, both in TAO patients and in healthy controls in a time-dependent manner ( Figures 4B, C ).…”
Section: Resultsmentioning
confidence: 99%